If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8x + -60 = 4 Reorder the terms: -60 + -8x = 4 Solving -60 + -8x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + -8x = 4 + 60 Combine like terms: -60 + 60 = 0 0 + -8x = 4 + 60 -8x = 4 + 60 Combine like terms: 4 + 60 = 64 -8x = 64 Divide each side by '-8'. x = -8 Simplifying x = -8
| 2x-36=-44 | | 14x-64=90 | | 20x-3=71 | | x^2+12x=-2 | | -52x-18=86 | | x^3+3x^2-2x=0 | | x(x)+7x+6=0 | | x(x)-2x+1=0 | | -4x+17=86 | | 4p(p)+8p=0 | | 10x-30=-80 | | (2b+1)(2b+1)=25 | | -5x+6y=69 | | 15x+17=-73 | | -6x-63=-75 | | -6-63=-75 | | x^3-6x-9=0 | | 3(x^2)+32x+45= | | x(x)-x-20=0 | | 30(x^2)+37x+10= | | 16=4(x-5)2 | | x(x)+12x-13=0 | | 8xy-120(x^2)(y^4)= | | x(x)-8x+12=0 | | (t+2)(t+2)=4 | | (t+2)2=4 | | 28-5x=4x+8 | | y=12x^2+203x+7 | | (6x+5)(4x+8)= | | 4x^2+6x+7=0 | | 3(n+1)=2(n+4) | | (-6x^2+10x+8)+(-8x^2+2x+6)= |